O`ZBEKISTON VA MARKAZIY OSIYONING TA’LIM SOHASIDAGI ALOQALARI VA ULARNING HAMKORLIK MASALALARI - Djumabayev Yorqin Turdibekovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article attempts to shed light on the processes of mutual cooperation, relations and development of the Republic of Uzbekistan with the countries of Central Asia in the field of education based on historical foundations, facts, and statistical data.